A fuzzy best–worst method (BWM) to assess the potential environmental impacts of the process of ship recycling. Issue 3 (3rd April 2022) - Soner, Omer; Celik, Erkan; Akyuz, Emre
ABSTRACT: The marine environment has been under threat due to the residues and pollution created during the ship recycling process. Materials contained in ship structure or equipment are the main concern that causes pollution of soil, air, marine, and freshwater resources at the ship recycling process. Accordingly, chemical and biological contaminants that may be released to the environment are the main elements of the ship recycling process. The emphasis of this research is therefore on the assessment of materials found in the ship structure or equipment of hazardous materials. To do so, this paper has applied the best–worth method (BWM) using fuzzy sets. The sets are based on surveys and questionnaires answered by industry experts. The findings of the research show that H4 (heavy metal residues) (H6) (polychlorinated organic compounds (PCBs), tin compound tributyltin (TBT), and asbestos (H3) are the most hazardous materials. Therefore, the study results also have the potential to assist professionals, policymakers, and regulatory authorities in the successful handling of hazardous materials that may release into the environment during the recycling process of ships. Consequently, the research provides a robust analytical model to assess the actual hazardous materials for the prevention and control of environmental pollution.